Assessing Performance in Simulated Cleft Palate Repair Using a Novel Video Recording Setup. (June 2020) - Podolsky, Dale J.; Fisher, David M.; Riff, Karen W. Wong; Zuker, Ronald M.; Drake, James M.; Forrest, Christopher R.
Objective: To test the feasibility of implementing a high-fidelity cleft palate simulator during a workshop in Santiago, Chile, using a novel video endoscope to assess technical performance. Design: Sixteen cleft surgeons from South America participated in a 2-day cleft training workshop. All 16 participants performed a simulated repair, and 13 of them performed a second simulated repair. The repairs were recorded using a low-cost video camera and a newly designed camera mouth retractor attachment. Twenty-nine videos were assessed by 3 cleft surgeons using a previously developed cleft palate objective structured assessment of technical skill (CLOSATS with embedded overall score assessment) and global rating scale. The reliability of the ratings and technical performance in relation to minimum acceptable scores and previous experience was assessed. Results: The video setup provided acceptable recording quality for the purpose of assessment. Average intraclass correlation coefficient for the CLOSATS, global, and overall performance score was 0.69, 0.75, and 0.82, respectively. None of the novice surgeons passed the CLOSATS and global score for both sessions. One participant in the intermediate group, and 2 participants in the advanced group passed the CLOSATS and global score for both sessions. There were highly experienced participants who failed to pass the CLOSATS and global score for both sessions. Conclusions: The cleft palate simulator can be practically implemented with video-recording capability to assess performance in cleft palate repair. This technology may be of assistance in assessing surgical competence in cleft palate repair.